Pulmonary Artery Catheter Use and Mortality in the Cardiac Intensive Care Unit - Kadosh, Bernard S; Berg, David D; Bohula, Erin A; Park, Jeong-Gun; Baird-Zars, Vivian M; Alviar, Carlos; Alzate, James; Barnett, Christopher F; Barsness, Gregory W; Burke, James; Chaudhry, Sunit-Preet; Daniels, Lori B; et al. (JACC. Heart failure, 2023)
The appropriate use of pulmonary artery catheters (PACs) in critically ill cardiac patients remains debated. The authors aimed to characterize the current use of PACs in cardiac intensive care units (CICUs) with attention to patient-level and institutional factors influencing their application and explore the association with in-hospital mortality. The Critical Care Cardiology Trials Network is a multicenter network of CICUs in North America. Between 2017 and 2021, participating centers contributed annual 2-month snapshots of consecutive CICU admissions. Admission diagnoses, clinical and demographic data, use of PACs, and in-hospital mortality were captured. Among 13,618 admissions at 34 sites, 3,827 were diagnosed with shock, with 2,583 of cardiogenic etiology. The use of mechanical circulatory support and heart failure were the patient-level factors most strongly associated with a greater likelihood of the use of a PAC (OR: 5.99 [95% CI: 5.15-6.98]; P < 0.001 and OR: 3.33 [95% CI: 2.91-3.81]; P < 0.001, respectively). The proportion of shock admissions with a PAC varied significantly by study center ranging from 8% to 73%. In analyses adjusted for factors associated with their placement, PAC use was associated with lower mortality in all shock patients admitted to a CICU (OR: 0.79 [95% CI: 0.66-0.96]; P = 0.017). There is wide variation in the use of PACs that is not fully explained by patient level-factors and appears driven in part by institutional tendency. PAC use was associated with higher survival in cardiac patients with shock presenting to CICUs. Randomized trials are needed to guide the appropriate use of PACs in cardiac critical care.